2010
DOI: 10.1111/j.1551-2916.2010.03778.x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Transmission Electron Microscopy of Electric Field‐Triggered Reversible Domain Formation in Bi‐Based Lead‐Free Piezoceramics

Abstract: A lead‐free piezoelectric 0.91(Bi1/2Na1/2)TiO3–0.06BaTiO3–0.03(K0.5Na0.5)NbO3 ceramic with high strain was examined in situ under an applied electric field using the transmission electron microscope. No domain structure is observed without an electric field, but an alternating electric field leads to the reversible formation of a lamellar domain structure. Correlations to polarization and strain hysteresis loop measurements indicate an electric field‐induced phase transition from a nonpolar to a ferroelectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
101
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(119 citation statements)
references
References 27 publications
15
101
0
Order By: Relevance
“…1(d), it can be seen that the intensities of these 1 = 2 (310) PC superlattice reflections remained measurable at room temperature. This is consistent with previous transmission electron microscopy (TEM) 37,38 and neutron diffraction 36 studies which revealed the coexistence of dominant a À a À a À -tilted (R3c) and small volume fractions of a 0 a 0 c þ -tilted (P4bm) structures for MPB (1 À x)NBT-xBT. At room temperature, the dominant phase of 0.944NBT-0.056BT was R3c, with P r ¼ 46.4 lC/cm 2 .…”
Section: Resultssupporting
confidence: 80%
“…1(d), it can be seen that the intensities of these 1 = 2 (310) PC superlattice reflections remained measurable at room temperature. This is consistent with previous transmission electron microscopy (TEM) 37,38 and neutron diffraction 36 studies which revealed the coexistence of dominant a À a À a À -tilted (R3c) and small volume fractions of a 0 a 0 c þ -tilted (P4bm) structures for MPB (1 À x)NBT-xBT. At room temperature, the dominant phase of 0.944NBT-0.056BT was R3c, with P r ¼ 46.4 lC/cm 2 .…”
Section: Resultssupporting
confidence: 80%
“…In fact, this is consistent with our previous observations that freshly sintered samples are free of ferroelectric domains, 34 and they are only observable on the application of a certain amount of electric field. 42 On the other hand, it should also be noted that the induced poled state of the currently investigated material is not stable enough to induce a remanent strain on the removal of the electric field and is disrupted completely at zero field. It was proposed that this absence of remanent strain possibly caused by a destabilization of electric-field-induced ferroelectric order at zero field be the origin of the large actuating performance featured by the large signal d 33 of ϳ550 pm/ V. 36 Thereby, it is very useful to introduce a parameter that can best-characterize the stability of ferroelectric order.…”
Section: Resultsmentioning
confidence: 99%
“…2 Furthermore, recent investigations of Na 1/2 Bi 1/2 TiO 3 -xat.%BaTiO 3 (NBT-x%BT) have revealed giant strain and longitudinal piezoelectric constants as high as d 33 ¼ 500 pC/N for compositions near a morphotropic phase boundary (MPB) around x ¼ 5.5-6.5. [3][4][5][6][7][8][9][10][11][12][13] In spite of a non-rhombohedral average structure model for NBT at room temperature was supported by highresolution single-crystal x ray diffraction, 14 it is still widely accepted that NBT undergoes a phase transformational sequence of paraelectric cubic (C) ! paraelectric tetragonal (T) !…”
mentioning
confidence: 99%